Can fisheries be "regenerative"? Adapting agroecological concepts for fisheries and the blue economy - Philip A. Loring (Canadian Science Publishing, 2023)
Regenerative design, in which agricultural practices are organized to work with nutrient cycles and successional processes, is increasingly being explored in food systems research and practice. In this commentary, I explore whether regenerative design concepts can be adapted to marine contexts, given increased global interest in the potential of marine ecosystems to support sustainable development, i.e., the blue economy. There are numerous fundamental ecological differences between terrestrial and marine ecologies that make it difficult to directly translate regenerative farming's focus on managing the nutrient cycle. However, building on a framework for regenerative food systems that focuses on how production activities are organized rather than the specific practices and technologies in use, I find multiple useful parallels to familiar patterns in the fisheries literature, specifically, fishing down the food web, poverty traps, and portfolio-based fishing. I conclude with a discussion of directions for research on regenerative fisheries and concerns regarding the potential for greenwashing under the banner of a regenerative blue economy.